(untitled) (Historia, 2021)
The current interest in “colonial” matters– often without clear definition – still identifies itself in this country by a handful of tired clichés. Pertinent words and phrases are (in)visibly highlighted and thereby set apart from others, as though by habit, and can be used to build up politically correct, if historically dubious, accounts of past (in)justices framed with seemingly heartfelt indignation.Professional historians and other scientists, who write also for the lay readership, are usually aware of crossing frontiers of credibility. Their readers, however, are not often as well informed, or frank, and may willingly embrace what they view as self-evident fact, rather than not-so-evident fantasy. Recently the remains of Saartjie Baartman, the “Hottentot Venus” (d.1815), were interred in the Eastern Cape during a thoughtfully managed ceremony. Memorials, whether contemporaneous or anachronous, are part of the very human awareness of (im)mortality, and modern history records a continuous cycle of such ex/inhumations. Grave robbers once were severely punished for their nocturnal researches undertaken in the lamplight of learning. By the 19th century this shadowed process had evolved into legitimate inquiry through scientific institutions in Western capitals such as Paris, Amsterdam, London, New York and, not surprisingly, Berlin.